2021
DOI: 10.26434/chemrxiv.14611146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepPocket: Ligand Binding Site Detection and Segmentation using 3D Convolutional Neural Networks

Abstract: <div> A structure-based drug design pipeline involves the development of potential drug molecules or ligands that form stable complexes with a given receptor at its binding site. A prerequisite to this is finding druggable and functionally relevant binding sites on the 3D structure of the protein. Although several methods for detecting binding sites have been developed beforehand, a majority of them surprisingly fail in the identification and ranking of binding sites accurately. The rapid adoption and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Such a tool could provide more freedom of choice for this parameter. The work of Aggarwal et al (2021), among others, has shown that many pieces of software for pocket identification tend to identify large pockets without segmentation techniques. Segmentation could be used to find subpockets that are better suited to virtual screening and docking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a tool could provide more freedom of choice for this parameter. The work of Aggarwal et al (2021), among others, has shown that many pieces of software for pocket identification tend to identify large pockets without segmentation techniques. Segmentation could be used to find subpockets that are better suited to virtual screening and docking.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the focus is on characterizing protein-protein interfaces (PPI) to allow designing of PPI disruptors. The capabilities of convolutional neural networks were boosted by pocket segmentation in Aggarwal et al (2021). This work and others [e.g., Stepniewska-Dziubinska et al (2020)] demonstrated that both prediction and other activities, such as segmentation, are beneficial, so one can devise a more complex framework than a pure predictor.…”
Section: Introductionmentioning
confidence: 93%
“…Traditional computational methods for scanning proteins for their most "druggable" areas have leveraged various views such as utilizing the protein's 3D structure or/and residue sequence, extracting geometric features, building large template libraries, or relying on energy-based models (Macari et al, 2019). Recently, DL changed this paradigm, e.g., using 3D CNNs (Aggarwal et al, 2021;Jiménez et al, 2017;Torng & Altman, 2019b) or sequence models (Sankararaman et al, 2010).…”
Section: Related Workmentioning
confidence: 99%
“…Inspired by the previous studies [15][16][17], in this work, we mainly focused on rebuilding the CNN model using a more accurate model, and enlarging the training set to further optimize the model performance. Previous reports adopted different versions of scPDB dataset for training the deep learning model [15][16][17]20].…”
Section: Introductionmentioning
confidence: 99%